PARTISIPASI PEREMPUAN DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA PADA ORGANISASI PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DI DESA BALI 1, KECEMATAN DOMPU - Mirnawati; Masyhuri; Sumitro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Family welfare issues remain an important concern in community development, particularly in rural areas. Limited access to economic opportunities, education, and health services positions the family as a unit that needs to be empowered sustainably. One of the efforts undertaken by the government to improve family welfare is through the Family Empowerment and Welfare Organization (PKK), which involves women as the main actors in social development at the village level. Women’s participation in PKK activities is expected to encourage improvements in the quality of life of families and the wider community. This study aims to describe the forms of women’s participation in PKK activities and to analyze their impact on improving family welfare in Bali 1 Village, Dompu District. This research employed a qualitative approach using a case study method. The research subjects consisted of nine PKK members, while the key informants comprised three individuals, namely the Village Head, the Head of the Village PKK, and the Head of the Subdistrict Social Welfare Section. Data collection techniques included in-depth interviews, field observations, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. he results of the study indicate that women’s participation in PKK activities is manifested in various forms, including participation in ideas, labor, financial contributions, moral support, and skills. Such participation contributes positively to the improvement of family welfare in economic, social, health, and educational aspects. Therefore, the existence of PKK plays a strategic role in empowering women and enhancing the quality of family life at the village level.